Lysosomal and peroxisomal disorders producing leukodystrophies - Cecil, Kim M.; Lindquist, Diana M. (Journal of Pediatric Neuroradiology, 2013)
Lysosomes are organelles within a cell responsible for breaking down waste materials and cellular debris. There are approximately forty known inherited disorders with primary lysosomal defects affecting the metabolism of lipids, glycoproteins, and mucopolysaccharides. Peroxisomes are organelles within a cell that are responsible for the biosynthesis of membrane phospholipids (plasmalogens), cholesterol, and bile acids, conversion of amino acids into glucose, oxidation of fatty acids, reduction of hydrogen peroxide by catalases, and prevention of excess oxalate synthesis. Lysosomal and peroxisomal disorders can produce leukodystrophies. Magnetic resonance imaging and proton magnetic resonance spectroscopy can provide important information in evaluating patients with concern for a possible inherited metabolic disorder, initially by narrowing the differential diagnosis of patients with suspected leukodystrophies and subsequently by monitoring disease progression. Lysosomal and peroxisomal disorders can be challenging, as some phenotypes may represent residual cellular activity of the organelle and initially present with normal imaging. However, the goal of the authors in this article is to provide an overview of known lysosomal and peroxisomal disorders producing leukodystrophies. In this article, we discuss the imaging features of three lysosomal disorders and four peroxisomal disorders, respectively, which can also be classified as leukodystrophies.
Keywords: Brain; magnetic resonance spectroscopy; leukodystrophy; white matter disease; neurons; axons; myelin; organelle; lysosome; peroxisome